FcrR3A -158 Polymorphism and Stromal Tumor-Infiltrating Lymphocytes and Survival among Patients with Metastatic HER2-Positive Breast Cancer Receiving Trastuzumab-Based Treatment - Chae, Heejung; Yoo, Changhoon; Yoon, Jung-A; Lee, Hee Jin; Kim, Kyu-pyo; Kim, Jeong-Eun; Ahn, Jin-Hee; Jung, Kyung Hae; Gong, Gyungyub; Kim, Sung-Bae (Journal of breast cancer, 2018)
The prognosis of human epidermal growth factor receptor 2 (HER2)-positive breast cancer has markedly improved since the introduction of trastuzumab. We aimed to evaluate the association between stromal tumor-infiltrating lymphocyte (sTIL) or polymorphisms and survival among patients with metastatic HER2-positive breast cancer who were treated with trastuzumab. A total of 56 women with recurrent or metastatic HER2-positive breast cancer who received the trastuzumab-taxane combination as first-line treatment were included in this retrospective analysis. The single-step multiplex allele-specific real-time polymerase chain reaction technique was employed for genotyping. sTILs were identified via immunohistochemical analysis of surgical (n=34, 60.7%) or biopsy specimens of metastatic lesions (n=22, 39.3%). We classified patients based on the sTIL level (≤10% [n=44] or >10% [n=12]); high sTIL counts were more commonly observed in patients with hormone receptor-negative tumors than in those with hormone receptor-positive tumors (34.8% vs. 12.1%, =0.02). There was a significant association between high sTIL levels and longer progression-free survival in comparison to low sTIL levels (median, 28.4 months vs. 16.8 months; =0.03). With regard to the -158 genotype, patients were classified into the Phenylalanine/Phenylalanine group (23 patients, 41.1%), Phenylalanine/Valine group (23 patients, 41,1%), or Valine/Valine group (10 patients, 17.9%); these classifications were not associated with clinical outcomes. High sTIL expression may be associated with better efficacy of trastuzumab-containing therapy in patients with metastatic HER2-positive breast cancer. However, this finding warrants further evaluation in the larger population.